2022
DOI: 10.18502/kss.v7i14.12039
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Social Reporting of Islamic Banking in Indonesia

Abstract: The objective of this study was to determine the influence of profitability, liquidity, company size, and leverage on the disclosure of Islamic social reporting (ISR) of Islamic banking in Indonesia. The period of research was 2016-2019 and a quantitative approach was used. The sample included 32 financial reports from 8 Islamic commercial banks in Indonesia registered with the Financial Services Authority for the period 2016-2019, and these were selected by purposive sampling. Data were analyzed through multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Some of the results of these studies were influenced by factors that varied or were inconsistently identified by different researchers. This is supported by the first (Jati et al, 2020), fourth (So et al, 2021), and fifth (Diansari et al, 2022) researchers who obtained different results for the leverage variable, the first researcher found that the results had no effect, while the fourth and fifth researchers found influential results.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Some of the results of these studies were influenced by factors that varied or were inconsistently identified by different researchers. This is supported by the first (Jati et al, 2020), fourth (So et al, 2021), and fifth (Diansari et al, 2022) researchers who obtained different results for the leverage variable, the first researcher found that the results had no effect, while the fourth and fifth researchers found influential results.…”
Section: Introductionmentioning
confidence: 71%
“…Apart from that, for the profitability variable, differences were found in the results of the sixth researcher (Ben Abdallah & Bahloul, 2022) and other researchers who were used as references in this research, where the researcher (Ben Abdallah & Bahloul, 2022) found that the ratio of profitability, namely ROA, had an effect. negative, while the research results from the first researcher (Jati et al, 2020) and the fifth researcher (Diansari et al, 2022) revealed that ISR disclosure was not affected by ROA as a ratio of profitability. With this research gap, researchers are encouraged to carry out testing again.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations